The Effectiveness of Task-Based Language Teaching to Teach Speaking Skills - Lume Lume Lume; Muh. Hisbullah (Journal of Languages and Language Teaching, 2022)
This study aims to find out the effectiveness of task-based language teaching to enhance speaking skills. It applied a method to teach speaking skills in SMK NW Darul Abror Kuta in Central Lombok. The research objectives are to know whether tasks-based language teaching is effective in teaching students speaking skills at ten-grade SMK NW Darul Abror Kuta in the academic year of 2020/2021. The research was conducted in six meetings, the first meeting was given a pre-test and the second meeting until the fifth meeting for giving treatment with the descriptive text material, and six sessions to give a post-test. The researcher uses Quasi-Experimental Design. The population of the research was 127 students. The researcher used random cluster sampling to take the sample, and the samples of this research were eleventh-grade students of XI B as an experimental group that would be taught by using task-based language teaching and XI D as a control group would be taught by using the direct method. In experimental group consisted of 29 students, while the control group consisted of 30 students. The data was taken by test and analyzed by independent t-test. The mean score of students in the experimental group taught using Task-Based Language Teaching is 66.38. In the control group, the mean score of students taught using the direct method is 60.3. The results of t-test computation, to was 3.079 while tt with the degree of freedom 57 in the level of significance 0.05, therefore, towas higher than tt. It means the alternative hypothesis is accepted; Task-Based Language Teaching is Effective to teach speaking skills.